The effect of interaction between macromolecule supplement and oxygen tension on bovine oocytes and embryos cultured in vitro - Mingoti, Gisele Zoccal [UNESP]; Castro, V. S. D. Caiado [UNESP]; Meo, S. C.; Barretto, L. S. S. [UNESP]; Garcia, J. M. [UNESP] (Cambridge University Press, 2009)
Aiming to improve in vitro production of bovine embryos and to obtain supplements to replace serum for in vitro maturation (IVM.), this study evaluated the effects of macromolecular supplementation of IMV medium (bovine serum albumin - BSA, polyvinyl alcohol - PVA, polyvinyl pyrrolidone - PVP, Ficoll, KnockoutSR, or fetal calf serum - FCS) and oxygen tension [5% CO(2) in air (20% O(2)) or 5% CO(2), 5% O(2) and 90% N(2) (5% O(2))] on oocyte maturation and embryo development. Nuclear progression to germinal vesicle breakdown, metaphase I and metaphase II stages were evaluated and overall results revealed that undefined (FCS) and semi-defined (BSA) media gave better results at 20% O(2) and defined media (PVA, PVP and Ficoll) at 5% O(2). Independent of macromolecule supplement, IVM at 20% O(2) was considered optimal for nuclear maturation. To evaluate embryo development, oocytes matured in the previously described conditions were fertilized and cultured at the same oxygen tension used for IVM and assessed for cleavage (43.0 to 74.8%) and development to morulae (16.4 to 33.8%), blastocyst (7.7 to 52.9%) and hatched blastocyst (9.6 to 48.1%). Apart from oxygen tension, all treatments, except Knockout (22.7%), gave similar results for blastocyst development (26.5 to 38.7%). Independently of macromolecule supplement, higher development rates were obtained in an oxygen tension of 20% O(2) (67.4% cleavage, 29.2%) morulae, 40.8% blastocyst and 34.0%, hatched blastocyst) when compared with 5% O(2) (52.5, 21.8, 18.2 and 15.6%, respectively). This study indicates that BSA, PVA, PVP and Ficoll can replace serum during IVM and that the optimal atmospheric condition for in vitro production of bovine embryos is 5% CO(2) and 20% O(2).
Keywords: Cattle; Embryo; Macromolecule; Maturation; Oocyte; Oxygen